Rab11B participates in erythrocyte storage lesion of under-collected whole blood. (April 2021) - Cai, Li; Zhang, Jingjing; Hongyun, Wu; Zhu, Yi; Zhang, Xiongfei; Liang, Wenbiao
Highlights: A new mechanism for RBC storage lesion is proposed. The mechanism relies on Rab protein changes in erythrocyte membrane. Rab11B participates in the RBC storage lesion through Rab11B/V-ATPases pathways. Abstract: Background and Objectives: The storage lesion of the red blood cell affects the life span of RBC and the quality of blood component. The elucidation of this mechanism is helpful to reduce the storage damage of RBC and improve the efficacy and safety of blood transfusion. The aim of this study was to discover the potential molecular mechanism of erythrocyte storage lesion with Under-collected whole blood (UC-WB) model. Methods: The label-free MS/MS quantitative method was used to identify the differential proteins of erythrocyte membrane proteins and the difference of Rab11B, V-ATPase and plasma GDI2 protein expression were further verified by western blot at the end of blood storage. Results: A total of 12 Rab proteins and 3 interacting effector proteins were identified among the membrane protein of normal WB and UC-WB, including 5 differential Rab proteins and 2 interacting effector proteins. Compared with normal WB, the expression of membrane Rab11B protein and ATP6V1B1/2 subunit of V-ATPases protein as well as the plasma GDI2 protein of UC-WB increased at the end of storage period. Conclusion: Rab protein might be related to RBC storage lesions, Rab11B participates in the RBC storage lesion through Rab11B/V-ATPases pathways.